In-hospital mortality among neonates with necrotising enterocolitis in Ethiopia: a systematic review and meta-analysis - Addisu Getie; Adam Wondmieneh; Melaku Bimerew; Manay Ayalneh; Freweyni Gebreegziabher Araya; Nigatu Dessalegn (BMJ Open)
Objective To assess the pooled in-hospital mortality among neonates with necrotising enterocolitis (NEC) in Ethiopia.Design This was a systematic review and meta-analysis reported based on the Preferred Reporting Items for Systematic Review and Meta-analysis guideline.Data sources African Journals Online, PubMed/Medline, Google Scholar, Cochrane Library and repositories of Ethiopian Universities.Eligibility criteria Published and unpublished articles that had reported the in-hospital mortality among neonates with NEC in Ethiopia were included, whereas, articles with no abstracts and/or inaccessible full texts, citations, reviews, commentaries editorials, conference abstracts, anonymous reports and articles reported in non-English language were excluded.Data extraction and synthesis Articles that passed the eligibility criteria were assessed for their quality using the quality appraisal criteria for prevalence studies. Data extraction and cleaning were done by using the Microsoft Excel work sheet, and data were analysed by STATA V.11.0 using the random effects model at 95% CI. Test of heterogeneity, publication bias, sensitivity analysis, subgroup analysis and meta-regression were performed.Results A total of 12 articles involving 588 neonates were included. The pooled in-hospital mortality among neonates with NEC in Ethiopia was found to be 70.0% (95% CI=60.0% to 80.0%; I2=87.5%). There was significant difference in mortality by study population as the in-hospital mortality among neonates with NEC was 83.0% (95% CI=76.0% to 89.0%; I2=42.8%; five studies) in preterm neonates and 73.0% (95% CI=60.0% to 86.0%; I2=66.3%; four studies) in low birthweight neonates (p<0.001).Conclusion The in-hospital mortality of neonates with NEC in Ethiopia was found to be high in which 7 out of 10 neonates diagnosed with NEC ends with death. Therefore, the currently available NEC prevention strategies should be evaluated for individual units and introduced where possible.